Sodium-ion battery positive electrode material containing various light metal ions and having P2P3 composite structure as well as preparation method and application of sodium-ion battery positive electrode material
By introducing a composite structure of P2 and P3 phases into the positive electrode material of sodium ion battery and combining a combination of light metals and transition metals, the disadvantages of existing materials in terms of both cyclic performance and electrochemical capacity are solved, and the specific capacity and cycle life of the material are significantly improved.
Patent Information
- Application Number
- CN202510008307.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
The existing sodium ion battery P-type structure positive electrode materials have disadvantages in terms of both cyclic performance and electrochemical capacity, and the material is prone to complex phase transformation during charging and discharging, the structure is unstable, and the circulation performance is poor.
By introducing the composite proportion optimization of P2 and P3 phases and combining a combination of a variety of light metals and transition metals, a sodium ion battery positive electrode material that takes into account cyclic stability and electrochemical capacity improvement was designed. This material suppresses phase change through structural locking effect, improving the stability and electrochemical properties of the material.
The specific capacity and cycle life of the material have been significantly improved, the specific discharge capacity has been increased by 27-35%, and the discharge capacity retention rate has been increased by 53-60% after 100 weeks of circulation. The structural stability of the material and the cycle stability of the battery have been significantly improved.
Smart Images

Figure CN119764422A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to a sodium ion battery positive electrode material with a P2&P3 composite structure, and a preparation method and application thereof. Background Art
[0002] Existing energy storage technologies, such as lithium-ion batteries, are difficult to meet the needs of large-scale applications due to resource limitations and cost issues.
[0003] The emergence of sodium-ion battery technology provides a possible solution to this problem. Sodium-ion batteries are a new type of energy storage system that uses the migration of sodium ions between positive and negative electrodes to store and release energy. Compared with lithium-ion batteries, sodium-ion batteries have many potential advantages. First, the abundance of sodium in the earth's crust is much higher than that of lithium, making sodium-ion batteries cheaper to manufacture. Second, the charging and discharging mechanism of sodium-ion batteries is similar to that of lithium-ion batteries, so existing lithium-ion battery technology can be used for development. In addition, sodium-ion batteries also have a wider operating temperature range and higher safety, making them more competitive in various application scenarios.
[0004] The cathode material is a key component of sodium-ion batteries, which determines key parameters such as battery energy density, charge and discharge performance, and cycle life. However, the cathode materials for sodium-ion batteries currently on the market, such as Prussian blue compounds, polyanion structures, and layered oxide materials, have their own advantages and disadvantages. Among them, the disadvantages of poor structural stability, low capacity, and short cycle life limit the practical application of sodium-ion batteries.
[0005] Layered oxide cathode materials are a hot topic of research. They have unique crystal structures and excellent electrochemical properties, and can provide high energy density and stable charge and discharge performance. In addition, by adjusting the composition and structure of the materials, the performance of sodium-ion batteries can be finely controlled.
[0006] In the existing sodium-ion battery layered oxide positive electrode material system, the materials can be divided into O-type and P-type structures according to their different structures, and can be divided into "2" or "3" structures according to the different minimum stacking repeating units, such as O2, O3, P2 and P3 structures. These different types of layered oxide materials provide more choices and possibilities for the performance optimization of sodium-ion batteries.
[0007] P-type structured materials have the disadvantage that they cannot have both cycle performance and electrochemical capacity: when cycle stability is used as the design goal, the electrochemical capacity is low; when electrochemical capacity is used as the design goal, cycle stability will be sacrificed.
[0008] Although some studies have been conducted on the composite structures of layered oxides for sodium-ion batteries, such as Chinese Patent Application CN114156444A which studied the O3 phase and P2 phase composite technology, and Chinese Patent Application CN117164016A which introduced the P'3, P2, and P3 composite structure technology containing Ni, Mn, Co, and Cu; however, these technologies lack clear regulation of the composite phase ratio and do not effectively solve the problem of the stability of continuous phase transformation during charge and discharge. In addition, the improvement of the long-cycle performance of their materials is limited.
[0009] To solve the above technical problems, this application optimizes the composite ratio of the P2 and P3 phases and combines a variety of light metals and transition metals, not only significantly improving the specific capacity and cycle life, but also suppressing phase transformation through the structure locking effect, thereby overcoming the defects of the prior art. Summary of the Invention
[0010] To solve the above technical problems, the present invention proposes a new design and preparation method for a layered oxide cathode material, and then develops a sodium-ion battery cathode material that takes into account both cycle stability and electrochemical capacity improvement from the dual perspectives of element regulation and structure design for P-type materials.
[0011] Commonly developed P-type layered oxide cathode materials currently have problems such as low capacity, easy occurrence of complex phase transformations during charge and discharge, unstable structure during the electrochemical reaction process, and poor cycling performance. The inventors of the present invention have found through long-term research that the essence of solving these problems lies in element regulation, adjusting the structure, and stabilizing the phase transformation behavior of the crystal structure during charge and discharge, so as to improve the electrochemical performance of the material and enhance the capacity and cycle stability. For this reason, the present invention innovatively introduces a variety of light metal ions and on this basis introduces the concept of the composite of two structures, P2 and P3, so that the high stability of P2 and the high-capacity characteristics of P3 complement each other, thus ensuring the stability of the crystal structure of the cathode material, suppressing the destructive structure transformation of the material during the charge and discharge of the battery, and then greatly improving the electrochemical performance of the material and enhancing its capacity and cycle stability.
[0012] Therefore, the present invention provides a layered oxide sodium-ion battery cathode material containing a variety of light metal ions and having a P2&P3 composite structure, and the chemical formula of the cathode material is Na a Mn x Ni y M z O2, where 0.6 ≤ a ≤ 0.66, 0.5 ≤ x ≤ 0.75, 0.25 ≤ y ≤ 0.5, 0 < z ≤ 0.1, and M is one or more of the elements Li, K, and Mg. The cathode material has a structure composed of a hexagonal P2 phase and a hexagonal P3 phase in composite.
[0013] Preferably, the chemical formula of the sodium ion battery positive electrode material is Na a Mn x Ni y M z O2, where:
[0014] The preferred range of a is 0.6≤a≤0.66, or more preferably a=0.66;
[0015] The preferred range of x is 0.65≤x≤0.75, or more preferably x=0.675 and x=0.75;
[0016] The preferred range of y is 0.225≤y≤0.25, or more preferably y=0.225 and y=0.25;
[0017] The preferred range of z is 0.01≤z≤0.10;
[0018] M preferably includes light metals Li, K, Mg, K&Mg, K&Li.
[0019] Preferably, the positive electrode material has a composite structure of hexagonal P2 phase and P3 phase, wherein the molar proportion of the P2 phase is 20%-30%; and the molar proportion of the P3 phase is 70%-80%.
[0020] The present invention also provides a method for preparing the layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure, comprising the steps of:
[0021] (1) According to the chemical formula of the positive electrode material, a soluble metal salt of the corresponding transition metal, a precipitant and water are used to obtain a transition metal precursor through a precipitation reaction at a certain temperature;
[0022] (2) uniformly mixing the transition metal precursor, M source compound and sodium source compound obtained in step (1) to obtain a mixture;
[0023] (3) The mixture obtained in step (2) is subjected to high temperature sintering to obtain the layered oxide sodium ion battery positive electrode material having the P2&P3 composite structure.
[0024] Wherein, in the step (1), the soluble metal salt of the transition metal includes one or more of the sulfate, acetate, and nitrate of Ni, and one or more of the sulfate, acetate, and nitrate of Mn.
[0025] Wherein, in the step (1), the precipitant is one or more of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.
[0026] Wherein, in the step (1), the reaction temperature of the precipitation reaction is 40-70° C., and the reaction time is 10-30 hours.
[0027] Wherein, in step (2), the sodium source compound is at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0028] Wherein, in the step (2), the molar ratio of the amount of the sodium source compound added in terms of sodium to the transition metal precursor is 0.6 to 0.66: 1. Wherein, in the case of high temperature loss, an appropriate excess amount of the sodium source is added to compensate for the high temperature loss.
[0029] Wherein, in step (2), the M source compound includes at least one of a carbonate or an oxide of M, for example, at least one of lithium carbonate, potassium carbonate or magnesium oxide.
[0030] Wherein, in the step (3), the high temperature sintering atmosphere is an oxygen-containing atmosphere, such as air.
[0031] Wherein, in the step (3), the sintering system of the high temperature sintering is firstly heated to 300-500°C at a heating rate of 1-10°C / min, and kept warm for 3-7h; then heated to 750-850°C at a heating rate of 1-10°C / min, and kept warm for 10-60h.
[0032] The present invention also provides a battery positive electrode material, which includes the battery positive electrode material prepared by the above-mentioned method for preparing the layered oxide sodium ion battery positive electrode material with a P2&P3 composite structure.
[0033] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned layered oxide sodium ion battery positive electrode material with a P2&P3 composite structure.
[0034] The present invention has the following beneficial technical effects:
[0035] The present invention constructs a layered oxide sodium ion battery positive electrode material containing multiple light metal ions (the multiple light metal ions include Na ions and one or more of Li ions, K ions, and Mg ions) and having two structures P2 and P3 composited with each other by regulating the structural composition of the material.
[0036] By introducing a variety of light metal ions and P2&P3 structure composites into layered oxides, the high stability of P2 and the high capacity characteristics of P3 complement each other, thereby ensuring the stability of the crystal structure of the positive electrode material, inhibiting the destructive structural transformation of the material during the battery charging and discharging process, and thus greatly improving the electrochemical performance of the material, improving its capacity and cycle stability. In the voltage range of 2-4.5V, the discharge specific capacity increased by 27-35%, for example, from 128.2mAh / g to 166.55mAh / g, achieving a high discharge specific capacity of layered oxide sodium ion batteries. After 100 cycles, the discharge capacity retention rate increased by 53-60%, for example, from 36.96% to 93.19%, and the structural stability of the material and the cycle stability of the battery were significantly improved.
[0037] The combination of P2 phase and P3 phase in the material changes the traditional electronic structure of the material and stimulates the electrochemical activity of the material, thereby improving the specific capacity of the battery. The discharge specific capacity is increased by 27-35%, for example, from 128.2mAh / g to 166.55mAh / g.
[0038] At the same time, through the structural composite effect of P2 and P3, the mutual composite of the two structures produces a certain "locking effect" on the crystal structure of the material, which makes the material undergo a reversible and stable structural transformation during the process of sodium insertion and extraction, thereby inhibiting the structural collapse of the material during the cycle, thereby greatly improving the cycle performance of the battery, and the retention rate has increased by 53-60%, for example, from 36.96% to 93.19%. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The first week charge and discharge curves of the sodium ion battery positive electrode materials prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention.
[0041] Figure 2 This is a first-week charge and discharge curve diagram of the sodium ion battery positive electrode material prepared in Examples 1-5 of the present invention.
[0042] Figure 3 The charge and discharge cycle capacity retention rate curves of the sodium ion battery positive electrode materials prepared in Comparative Example 1, Comparative Example 2 and Examples 1-5 of the present invention.
[0043] Figure 4 It is the XRD diffraction curve of comparative example 1 in the present invention, as well as the result of refining and analyzing the XRD curve of the material using the Rietveld method, and its phase composition and proportion.
[0044] Figure 5It is the XRD diffraction curve of comparative example 2 in the present invention and the result of refining and analyzing the XRD curve of the material using the Rietveld method, as well as its phase composition and proportion.
[0045] Figure 6 It is the XRD diffraction curve of Example 1 in the present invention and the result of refining and analyzing the XRD curve of the material using the Rietveld method, as well as its phase composition and proportion.
[0046] Figure 7 It is the XRD diffraction curve of Example 2 in the present invention and the result of refining the XRD curve of the material using the Rietveld method and its phase composition and proportion.
[0047] Figure 8 It is the XRD diffraction curve of Example 3 in the present invention and the result of refining and analyzing the XRD curve of the material using the Rietveld method, as well as its phase composition and proportion.
[0048] Fig. 9 It is the XRD diffraction curve of Example 4 in the present invention and the result of refining the XRD curve of the material using the Rietveld method and its phase composition and proportion.
[0049] Fig.10 It is the XRD diffraction curve of Example 5 in the present invention and the result of refining the XRD curve of the material using the Rietveld method, as well as its phase composition and proportion. DETAILED DESCRIPTION
[0050] The present invention will be described in further detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only for illustration and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims of the present application.
[0051] Comparative Example 1:
[0052] Comparative Example 1 is a pure P3 type sodium ion battery layered oxide positive electrode material P3-Na 0.66 Ni 0.25 Mn 0.75 O2.
[0053] The preparation method comprises the following steps:
[0054] (1) dissolving manganese sulfate monohydrate and nickel sulfate hexahydrate in deionized water at a stoichiometric ratio of 3:1 to form a 2 mol / L solution; slowly adding a precipitant solution and ammonia water into a reaction kettle under high-speed stirring; wherein the concentration of sodium hydroxide in the precipitant solution is 2 mol / L, and the concentration of ammonia water is 3 mol / L; controlling the pH value to 10.6, controlling the water bath temperature to 55° C., reacting for 18 hours, filtering, washing, and drying to obtain a transition metal precursor material;
[0055] (2) Sodium carbonate and the above transition metal precursor material were uniformly mixed in a high-speed mixer at a molar ratio of 0.33:1, and the resulting mixture was placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 700°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a pure P3 type sodium ion battery layered oxide positive electrode material P3-Na 0.66 Ni 0.25 Mn 0.75 O2.
[0056] X-ray diffractometer (XRD) is used to analyze the phase of the material. Figure 4 Material P3-Na shown 0.66 Ni 0.25 Mn 0.75 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Figure 4 As shown, the pure P3 structure was obtained through refinement.
[0057] Preparation of sodium ion battery: The pure P3 type sodium ion battery layered oxide positive electrode material P3-Na prepared in Comparative Example 1 was 0.66 Ni 0.25 Mn 0.75 O2, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode. A metallic sodium sheet is used as a negative electrode, sodium perchlorate is used as an electrolyte salt, and propylene carbonate is used as an electrolyte solvent. The battery is assembled in a glove box to obtain a sodium ion battery.
[0058] The electrochemical performance of the sodium ion battery of Comparative Example 1 was tested using an electrochemical tester at a test temperature of 25°C. The initial charge and discharge performance of the battery was tested at a current density of 0.1C (1C = 160 mAh / g) and a voltage range of 2.0 to 4.5V. The performance results are as follows: Figure 1 As shown, the first charge and discharge specific capacities of comparative example 1 are 132.0 mAh / g and 133.0 mAh / g respectively. The cycle performance of the battery was tested at a 1C rate with a voltage range of 2.0 to 4.5 V. The performance results are shown in Figure 3As shown, the capacity retention rate is 36.96% after 100 cycles.
[0059] Comparative Example 2:
[0060] Comparative Example 2 is a pure P2 type sodium ion battery layered oxide positive electrode material P2-Na 0.66 Ni 0.25 Mn 0.75 O2.
[0061] The preparation method comprises the following steps:
[0062] (1) dissolving manganese sulfate monohydrate and nickel sulfate hexahydrate in deionized water at a stoichiometric ratio of 3:1 to form a 2 mol / L solution; slowly adding a precipitant solution and ammonia water into a reaction kettle under high-speed stirring, wherein the concentration of sodium hydroxide in the precipitant solution is 2 mol / L, and the concentration of ammonia water is 3 mol / L; controlling the pH value to 10.6, controlling the water bath temperature to 55° C., reacting for 18 hours, filtering, washing, and drying to obtain a transition metal precursor material;
[0063] (2) Sodium carbonate and the above transition metal precursor material were uniformly mixed in a high-speed mixer at a molar ratio of 0.33:1, and the resulting mixture was placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to be heated to 900°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a pure P2 type sodium ion battery layered oxide positive electrode material P2-Na 0.66 Ni 0.25 Mn 0.75 O2.
[0064] XRD is used to analyze the phase of the material, such as Figure 5 Material P2-Na shown 0.66 Ni 0.25 Mn 0.75 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Figure 5 As shown, the pure P2 structure was obtained through refinement.
[0065] Preparation of sodium ion battery: The pure P2 type sodium ion battery layered oxide positive electrode material P2-Na prepared in Comparative Example 2 was 0.66 Ni 0.25 Mn 0.75 O2, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode. A metallic sodium sheet is used as a negative electrode, sodium perchlorate is used as an electrolyte salt, and propylene carbonate is used as an electrolyte solvent. The battery is assembled in a glove box to obtain a sodium ion battery.
[0066] The electrochemical performance of the sodium ion battery of Comparative Example 2 was tested using an electrochemical tester at a test temperature of 25°C. The initial charge and discharge performance of the battery was tested at a current density of 0.1C (1C = 160 mAh / g) and a voltage range of 2.0 to 4.5V. The performance results are as follows: Figure 1 As shown, the first charge and discharge specific capacities of comparative example 1 are 122.26 mAh / g and 128.2 mAh / g respectively. The cycle performance of the battery was tested at a 1C rate with a voltage range of 2.0 to 4.5 V. The performance results are shown in Figure 3 As shown, the capacity retention rate is 42.69% after 100 cycles.
[0067] Embodiment 1:
[0068] Example 1 is a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure 0.6 K 0.05 Ni 0.25 Mn 0.75 O2.
[0069] The preparation method comprises the following steps:
[0070] (1) preparing a transition metal precursor material according to the same method as step (1) of Comparative Example 1;
[0071] (2) Sodium carbonate, potassium carbonate, and the aforementioned transition metal precursor material are weighed in a molar ratio of 0.30:0.025:1, and mixed in a high-speed mixer. The resulting mixture is then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept at this temperature for 5 hours, and then continued to be heated to 780°C at the same heating rate, kept at this temperature for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material P2&P3-Na with a P2&P3 composite structure. 0.6 Ni 0.25 Mn 0.75 O2.
[0072] XRD is used to analyze the phase of the material, such as Figure 6 Materials P2 & P3-Na shown 0.6 K 0.05 Ni 0.25 Mn 0.75 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Figure 6 As shown, through refinement, it is found that it is a composite structure of P2 and P3 phases, in which the P2 phase accounts for 24.24% of the material and the P3 phase accounts for 75.76%.
[0073] The layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure synthesized in Example 1 was prepared in the same manner as in Comparative Example 1. 0.6 K 0.05 Ni 0.25 Mn 0.75 O2 was used to prepare a sodium ion battery. The electrochemical performance of the sodium ion battery of Example 1 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 1 are shown in FIG. Figure 2 As shown in the graph, the first discharge capacity of Example 1 is increased to 155.44 mAh / g, and the electrochemical activity and specific capacity of the material are greatly improved. This is due to the presence of multiple light metal ions and the combination of P2 phase and P3 phase in the material, which changes the traditional electronic structure of the material and stimulates the electrochemical activity of the material, thereby improving the specific capacity of the battery. The cycle retention performance of Example 1 is shown in the graph. Figure 3 As shown, the capacity retention ability of the embodiment after 100 cycles is improved from 36.95% of comparative example 1 and 42.69% of comparative example 2 to 88.28%. It can be seen that the material stability and cycle stability of embodiment 1 are also greatly improved, which is due to the structural composite effect of P2 and P3. The mutual composite of the two structures has a certain "locking effect" on the crystal structure of the material, which makes the material undergo a reversible and stable structural transformation during the process of sodium insertion and deinsertion, thereby inhibiting the structural collapse of the material during the cycle, thereby greatly improving the cycle performance of the battery.
[0074] Embodiment 2:
[0075] Example 2 Preparation of a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure 0.6 K 0.05 Mg 0.01 Ni 0.25 Mn 0.75 O2.
[0076] The preparation method comprises the following steps:
[0077] (1) preparing a transition metal precursor material according to the same method as step (1) of Comparative Example 1;
[0078] (2) Sodium carbonate, potassium carbonate, magnesium oxide, and the aforementioned transition metal precursor material are weighed in a molar ratio of 0.30:0.025:0.01:1, and mixed uniformly in a high-speed mixer. The resulting mixture is then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept at this temperature for 5 hours, and then continued to be heated to 780°C at the same heating rate, kept at this temperature for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure. 0.6 K 0.05 Mg 0.01 Ni 0.25 Mn 0.75 O2.
[0079] XRD is used to analyze the phase of the material, such as Figure 7 Materials P2 & P3-Na shown 0.6 K 0.05 Mg 0.01 Ni 0.25 Mn 0.75 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Figure 7 As shown, through refinement, it is found that it is a composite structure of P2 and P3 phases, in which the P2 phase accounts for 25.29% of the material and the P3 phase accounts for 74.41%.
[0080] The P2 & P3-Na synthesized in Example 2 were prepared in the same manner as in Comparative Example 1. 0.6 K 0.05 Mg 0.01 Ni 0.25 Mn 0.75 O2 was used to prepare a sodium ion battery. The electrochemical performance of the lithium ion battery of Example 2 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 2 are shown in FIG. Figure 2 As shown in FIG. 1 , the first discharge capacity of Example 2 is increased to 159.83 mAh / g. The cycle retention performance of Example 2 is as follows: Figure 3 As shown, thanks to the presence of multiple light metal ions and the "locking effect" achieved after the structural combination of P2 and P3, the material structure achieves extremely impressive reversibility and stability during the sodium insertion and extraction process, and the capacity retention capacity of Example 2 after 100 cycles is improved to 93.19%. Similar to the effect of Example 1, the battery performance of Example 2 is also greatly improved compared with Comparative Examples 1 and 2.
[0081] Embodiment 3:
[0082] Example 3: Preparation of a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure 0.6 K 0.05 Li 0.01 Ni 0.25 Mn 0.75 O2.
[0083] The preparation method comprises the following steps:
[0084] (1) preparing a transition metal precursor material according to the same method as step (1) of Comparative Example 1;
[0085] (2) Sodium carbonate, potassium carbonate, lithium carbonate, and the aforementioned transition metal precursor material are weighed in a molar ratio of 0.30:0.025:0.005:1, and mixed in a high-speed mixer. The resulting mixture is then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 780°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure. 0.6 K 0.05 Li 0.01 Ni 0.25 Mn 0.75 O2.
[0086] XRD is used to analyze the phase of the material, such as Figure 8 Materials P2 & P3-Na shown 0.6 K 0.05 Li 0.01 Ni 0.25 Mn 0.75 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Figure 8 As shown, through refinement, it is found that it is a composite structure of P2 and P3 phases, in which the P2 phase accounts for 29.26% of the material and the P3 phase accounts for 70.74%.
[0087] The P2 & P3-Na synthesized in Example 3 were prepared in the same manner as in Comparative Example 1. 0.6 K 0.05 Li 0.01 Ni 0.25 Mn 0.75 O2 was used to prepare a sodium ion battery. The electrochemical performance of the lithium ion battery of Example 3 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 3 are shown in FIG. Figure 2As shown in FIG. 1 , the first discharge capacity of Example 3 is increased to 166.55 mAh / g. The cycle retention performance of Example 3 is as follows: Figure 3 As shown, thanks to the presence of multiple light metal ions and the "locking effect" achieved after the structural combination of P2 and P3, the material structure achieves extremely impressive reversibility and stability during the sodium insertion and extraction process, and the capacity retention capacity of Example 3 after 100 cycles is increased to 93.45%. Similar to the effects of Examples 1-2, the battery performance of Example 3 is also greatly improved compared with Comparative Examples 1 and 2.
[0088] Embodiment 4:
[0089] Example 4: Preparation of a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure 0.66 Ni 0.225 Mn 0.675 Li 0.1 O2.
[0090] The preparation method comprises the following steps:
[0091] (1) preparing a transition metal precursor material according to the same method as step (1) of Comparative Example 1;
[0092] (2) Sodium carbonate, lithium carbonate, the aforementioned transition metal precursor material, and lithium carbonate were weighed in a molar ratio of 0.33:0.05:1, and mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 780°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure. 0.66 Ni 0.225 Mn 0.675 Li 0.1 O2.
[0093] XRD is used to analyze the phase of the material, such as Fig. 9 Materials P2 & P3-Na shown 0.66 Ni 0.225 Mn 0.675 Li 0.1 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Fig. 9 As shown, through refinement, it is found that it is a composite structure of P2 and P3 phases, in which the P2 phase accounts for 29.56% of the material and the P3 phase accounts for 70.44%.
[0094] The P2 & P3-Na synthesized in Example 4 were prepared in the same manner as in Comparative Example 1. 0.66 Ni 0.225 Mn 0.675 Li 0.1 O2 was used to prepare a sodium ion battery. The electrochemical performance of the lithium ion battery of Example 4 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 4 are shown in FIG. Figure 2 As shown in FIG. 1 , the first discharge capacity of Example 4 is increased to 161.59 mAh / g. The cycle retention performance of Example 4 is as follows Figure 3 As shown, thanks to the presence of multiple light metal ions and the "locking effect" achieved after the structural combination of P2 and P3, the material structure achieves extremely impressive reversibility and stability during the sodium insertion and extraction process, and the capacity retention capacity of Example 4 after 100 cycles is improved to 92.93%. Similar to the effects of Examples 1-3, the battery performance of Example 4 is also greatly improved compared with Comparative Examples 1 and 2.
[0095] Embodiment 5:
[0096] Example 5 Preparation of layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure 0.66 Ni 0.225 Mn 0.675 Mg 0.1 O2.
[0097] The preparation method comprises the following steps:
[0098] (1) preparing a transition metal precursor material according to the same method as step (1) of Comparative Example 1;
[0099] (2) Sodium carbonate, the above transition metal precursor material, and magnesium oxide were weighed in a molar ratio of 0.33:1:0.1, and mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 780°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material P2&P3-Na containing multiple light metal ions and having a P2&P3 composite structure. 0.66 Ni 0.225 Mn 0.675 Mg 0.1 O2.
[0100] XRD is used to analyze the phase of the material, such as Fig.10 Materials P2 & P3-Na shown 0.66 Ni 0.225 Mn0.675 Mg 0.1 The XRD diffraction pattern of O2 was analyzed by GSAS software using the Rietveld method to refine the XRD curve of the material to obtain its phase composition and ratio. The results are as follows Fig.10 As shown, through refinement, it is found that it is a composite structure of P2 and P3 phases, in which the P2 phase accounts for 28.15% of the material and the P3 phase accounts for 71.85%.
[0101] The P2 & P3-Na synthesized in Example 5 were prepared in the same manner as in Comparative Example 1. 0.66 Ni 0.225 Mn 0.675 Mg 0.1 O2 was used to prepare a sodium ion battery. The electrochemical performance of the lithium ion battery of Example 4 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The first charge and discharge performance results of Example 5 are shown in FIG. Figure 2 As shown in FIG. 1 , the first discharge capacity of Example 5 is increased to 157.9 mAh / g. The cycle retention performance of Example 5 is as follows Figure 3 As shown, thanks to the presence of multiple light metal ions and the "locking effect" achieved after the structural combination of P2 and P3, the material structure achieves extremely impressive reversibility and stability during the sodium insertion and extraction process, and the capacity retention capacity of Example 5 after 100 cycles is improved to 91.26%. Similar to the effects of Examples 1-4, the battery performance of Example 5 is also greatly improved compared with Comparative Examples 1 and 2.
[0102] It can be seen from the above that compared with Comparative Example 1 containing only the P3 structure and Comparative Example 2 containing only the P2 structure, the specific capacity and cycle stability of the sodium ion battery prepared by the layered oxide sodium ion battery positive electrode material having a composite structure of P2 and P3 in Examples 1-5 have been greatly improved.
Claims
1. A layered oxide sodium-ion battery cathode material containing multiple light metal ions and having a P2&P3 composite structure, the chemical formula of the cathode material being Na a Mn x Ni y M z O2, where 0.6 ≤ a ≤ 0.66, 0.5 ≤ x ≤ 0.75, 0.225 ≤ y ≤ 0.25, 0 < z ≤ 0.1, and M is one or more of the elements Li, K, and Mg. The cathode material has a composite structure of a hexagonal P2 phase and a hexagonal P3 phase.
2. The layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 1, wherein: The M is the element Li, K or Mg, or the M is the element K and Mg, or the M is the element K and Li.
3. The layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 1, wherein: In the positive electrode material, the molar proportion of the P2 phase is 20%-30%; the molar proportion of the P3 phase is 70%-80%.
4. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2 & P3 composite structure as claimed in any one of claims 1 to 3, comprising the steps of: (1) According to the chemical formula of the positive electrode material, a soluble metal salt of the corresponding transition metal, a precipitant and water are used to obtain a transition metal precursor through a precipitation reaction at a certain temperature; (2) uniformly mixing the transition metal precursor, M source compound and sodium source compound obtained in step (1) to obtain a mixture; (3) The mixture obtained in step (2) is subjected to high temperature sintering to obtain the layered oxide sodium ion battery positive electrode material having the P2&P3 composite structure.
5. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 4, wherein: In the step (1), the precipitating agent is one or more of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.
6. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 4, wherein: In the step (2), the molar ratio of the amount of the sodium source compound added in terms of sodium to the transition metal precursor is 0.6 to 0.66:
1.
7. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 4, wherein: In the step (2), the M source compound includes at least one of a carbonate and an oxide of M.
8. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 4, wherein: In the step (3), the high temperature sintering process is as follows: firstly heating to 300-500°C and keeping the temperature for a certain period of time; then heating to 750-850°C and keeping the temperature for a certain period of time.
9. The method for preparing a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as claimed in claim 4, wherein: In the step (3), the high temperature sintering atmosphere is an oxygen-containing atmosphere.
10. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The positive electrode comprises a layered oxide sodium ion battery positive electrode material containing multiple light metal ions and having a P2&P3 composite structure as described in any one of claims 1-3.
Citation Information
Patent Citations
Preparation method of sodium ion battery positive electrode material with multiphase composite layered structure
CN108023082A
Sodium-ion battery positive electrode material with symbiotic layered structure as well as preparation method and application of sodium-ion battery positive electrode material
CN114156444A
Sodium layered oxide as sodium ion battery cathode material and manufacturing method thereof
CN114341059A
A P2 and P3 mixed-phase layered oxide cathode material for sodium-ion batteries, its preparation method and application
CN114937774A
Preparation method of nickel-manganese-based precursor and single-crystal layered positive electrode material of lithium / sodium ion battery
CN115432748A
Cited By
A sodium ion battery positive electrode material with a high-sodium honeycomb-type superlattice P2 / P3 composite structure, a preparation method and applications thereof
CN122739294A